A new fractional-order compartmental disease model - Luu Vu Cam Hoan; Akinlar, Mehmet Ali; Inc, Mustafa; Gomez-Aguilar, J. F.; Chu, Yu-Ming; Almohsen, Bandar (ELSEVIER, 2020)
In this paper, we propose a new SEIRS model and are concerned with stability and numerical solutions of the model. The model is generated under certain assumptions such as individuals are vaccinated or have a special treatment but do not carry lifelong immunity. After generating a new SEIRS model, we perturb the model into fractional time derivative form where Caputo type fractional-order derivative operators are employed. After showing existence and uniqueness of the non-negative solutions, we determine disease free steady-state point and basic reproduction number. We also determine endemic steady state points and study on stability of the fractional system in these equilibrium points. We solve fractional-order system approximately with an efficient Euler type numerical method. We conclude that the proposed system may serve as a kernel for understanding, analysis and computational solutions of a wide range of disease models in epidemiology. (C) 2020 The Authors. Published by Elsevier B.V. on behalf of Faculty of Engineering, Alexandria University.
Keywords: Frational SEIRS model; Stability analysis; Simulation; EQUATIONS; Engineering